Informatization of education: a review of theory and practice in Kazakhstan. (Journal of Educational Sciences, 2016)
To summarize trends in the development of education informatization we consider in the article the following questions: (1) general information on the level of computer literacy of the population of Kazakhstan; (2) understanding informatization of education and info communication individuals of student and teacher; (3) connectionism as a modern theory of informatization; (4) research in the field of information technologies in education in Kazakhstan. The purpose of the study is a review and synthesis of the theories of education informatization. The continuity of the scientific foundations of the modern theory of education: behaviorism – cognitivism – constructivism – connectionism is demonstrated. The issue of «cross-age development»: from reading generation in the twentieth century to the twenty-first century generation, receiving a large flow of visual information, is raised. Range of e-learning development and examples of the use of modern IT-technologies in Kazakhstan’s education are represented.
Keywords: informatization of individual; info communication individual; connectionism; computer literacy; scientific schools; information technologies in education